1998
DOI: 10.1007/bf02464804
|View full text |Cite
|
Sign up to set email alerts
|

Effects of delta-sleep-inducing peptide in cerebral ischemia in rats

Abstract: Experimental studies were carried out to investigate the neuroprotective effects of delta sleep-inducing peptide in animals with cerebral ischemia induced by bilateral compression of both carotid arteries, and to compare the efficacy of this peptide with that of MK-801. These studies led to the conclusion that the peptide had pronounced anti-ischemic effects, which were evident within 24 h and consisted of reductions in the severity of postural abnormalities in rats with bilateral cerebral ischemia, along with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 4 publications
0
3
0
1
Order By: Relevance
“…A neuroprotective effect has been demonstrated in rats subjected to bilateral carotid ligation [30]. A reduced mortality was observed together with a reduction in postischaemia function.…”
Section: Non‐sleep Effectsmentioning
confidence: 99%
“…A neuroprotective effect has been demonstrated in rats subjected to bilateral carotid ligation [30]. A reduced mortality was observed together with a reduction in postischaemia function.…”
Section: Non‐sleep Effectsmentioning
confidence: 99%
“…In Wistar rats, DSIP has been reported to reduce mortality, decrease the electrical activity of the brain, and increase cerebral blood flow in ischemic brain under conditions of global cerebral ischemia aggravated by pre-stress [4]. An even earlier study demonstrated a high potential of DSIP to reduce mortality when administered preventively 1 h before global cerebral ischemia in Wistar rats [5]. Given that KND is a more active analog of DSIP, it is of high interest to study its effect on the outcome of ischemia-reperfusion injuries that develop after transient myocardial infarction and transient focal cerebral stroke.…”
Section: Introductionmentioning
confidence: 99%
“…DSIP also has neuroprotective properties. Accordingly, the treatment of Wistar rats with DSIP several hours prior to global brain ischemia improved locomotor functions and reduced lethality [ 23 ]. DSIP reduced neuronal activity and improved blood supply of the brain of stressed animals subjected to brain ischemia [ 24 ].…”
Section: Introductionmentioning
confidence: 99%